1996
DOI: 10.1212/wnl.46.2.406
|View full text |Cite
|
Sign up to set email alerts
|

Familial and sporadic Alzheimer's disease

Abstract: Whether all etiologic forms of Alzheimer's disease (AD) share a final common pathway is a major issue. We determined the severity and regional distribution of neuronal loss, amyloid plaques, neuritic plaques (NPs), and neurofibrillary tangles (NFTs), and calculated the ratio of neuronal loss to NPs and NFTs in brains of 19 familial AD (FAD) patients with linkage to chromosome 14, six AD patients with mutations of chromosome 21 (codon 717 of the beta-amyloid percursor protein gene), and 11 sporadic AD (SAD) pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(67 citation statements)
references
References 31 publications
1
65
0
1
Order By: Relevance
“…Hallucinations and delusions were reported more frequently in PSEN1 A79V MCs from this family, as has been noted previously in individuals with ADAD. 44,45 These findings demonstrate that the clinical phenotypes of late-onset ADAD and LOAD can overlap, and suggest that previously reported clinical (e.g., seizures, early myoclonus, spastic paraparesis, dysarthria, and rapid decline [9][10][11][12][13][14][15][16][17][18] ) and neuropathological differences (e.g., altered cerebral Aβ 42 and neurofibrillary tangle deposition, increased prevalence of cerebral amyloid angiopathy, and formation of "cotton wool" plaques 6,12,16,[19][20][21][22][23][24][25][26][27] ) may reflect age-or mutation-dependent effects.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Hallucinations and delusions were reported more frequently in PSEN1 A79V MCs from this family, as has been noted previously in individuals with ADAD. 44,45 These findings demonstrate that the clinical phenotypes of late-onset ADAD and LOAD can overlap, and suggest that previously reported clinical (e.g., seizures, early myoclonus, spastic paraparesis, dysarthria, and rapid decline [9][10][11][12][13][14][15][16][17][18] ) and neuropathological differences (e.g., altered cerebral Aβ 42 and neurofibrillary tangle deposition, increased prevalence of cerebral amyloid angiopathy, and formation of "cotton wool" plaques 6,12,16,[19][20][21][22][23][24][25][26][27] ) may reflect age-or mutation-dependent effects.…”
Section: Discussionsupporting
confidence: 63%
“…7,8 Also, ADAD may be characterized by clinical features that are unusual in LOAD, including pyramidal signs, hypo/hyperkinetic movement disorders, ataxia, and early myoclonus and seizures. [9][10][11][12][13][14][15][16][17][18] Additional differences in the pattern of cerebral Aβ 42 deposition are reported in some ADAD cases, including 6,16,19,20 higher Aβ 42 burden and greater densities of neurofibrillary tangles; [21][22][23] increased Aβ 42 deposition within the cerebellum [24][25][26] and basal ganglia; 19,20 ; and higher prevalence of cerebral amyloid angiopathy and large diffuse so-called "cotton wool" plaques. 12,22,24,27 Such clinical and pathological differences may challenge whether findings from studies of early-onset ADAD, including current trials of anti-amyloid therapies, 28 can be extrapolated to the understanding of the far more common LOAD.…”
Section: Introductionmentioning
confidence: 99%
“…The postmortem pattern of amyloid deposition in PS1 mutation carriers with clinical dementia has been reported to be very similar to the pattern observed in sporadic AD (Lippa et al, 1996). Another postmortem study suggested that PS1 mutation carriers have similar loads of A␤ 40 -containing plaques and greater loads of A␤ 42(43) -containing plaques in their frontal cortex compared with sporadic AD cases (Mann et al, 2001).…”
Section: Discussionmentioning
confidence: 66%
“…Occasional neurofibrillary tangles were observed with X-34 histostaining in the neocortex but not in the striatum. Although Lippa et al (1996) previously noted that the overall grade of amyloid angiopathy was slightly greater in eoFAD than in sporadic AD, there was little or no cerebrovascular amyloid in the limited tissue samples available for examination for these two particular PS1 cases, although a previous postmortem study reported mild-to-moderate amyloid angiopathy in the frontal cortex of PS1 C410Y mutation carriers (Mann et al, 2001). …”
Section: Histological Analysis Of Postmortem Tissuementioning
confidence: 69%
See 1 more Smart Citation